2018
DOI: 10.1001/jamapediatrics.2018.0830
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Preprocedural Fasting With Outcomes of Emergency Department Sedation in Children

Abstract: ; for the Sedation Safety Study Group of Pediatric Emergency Research Canada IMPORTANCE It is not clear whether adherence to preprocedural fasting guidelines prevent pulmonary aspiration and associated adverse outcomes during emergency department (ED) sedation of children. OBJECTIVE To examine the association between preprocedural fasting duration and the incidence of sedation-related adverse outcomes in a large sample of children. DESIGN, SETTING, AND PARTICIPANTS We conducted a planned secondary analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 27 publications
0
46
2
1
Order By: Relevance
“…Indeed, there have been only two cases of aspiration reported in the emergency department setting; both patients had been fasted (2 hours liquids, 6 hours solids) before sedation, and both made a full recovery [20]. Multiple Emergency Department observational series have not identified any association between non-compliance with elective fasting guidelines and complications or adverse outcomes [11,[64][65][66][67][68][69][70][71].…”
Section: Acutely Ill or Injured Patients Presenting To Emergencymentioning
confidence: 99%
“…Indeed, there have been only two cases of aspiration reported in the emergency department setting; both patients had been fasted (2 hours liquids, 6 hours solids) before sedation, and both made a full recovery [20]. Multiple Emergency Department observational series have not identified any association between non-compliance with elective fasting guidelines and complications or adverse outcomes [11,[64][65][66][67][68][69][70][71].…”
Section: Acutely Ill or Injured Patients Presenting To Emergencymentioning
confidence: 99%
“…Two recent studies in the PED setting have evaluated the relationship between duration of preprocedural fasting and the risk of sedation‐related adverse events . In a multicenter prospective cohort study of sedation safety, 48.1% of the 6,166 children receiving procedural sedation did not meet fasting guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter prospective cohort study of sedation safety, 48.1% of the 6,166 children receiving procedural sedation did not meet fasting guidelines. There were no cases of clinically apparent pulmonary aspiration, and the authors found no association between fasting duration and any adverse event and concluded that “delaying sedation to meet established fasting guidelines does not improve sedation outcomes for children in the ED and is not warranted.” A nonrandomized before‐and‐after comparison of 2,188 children concluded that shortening preprocedural fasting from 6 to 3 hours did not result in increased vomiting and decreased ED length of stay . These studies suggest that fasting prior to procedural sedation may be unnecessary, particularly in otherwise low‐risk patients, when ketamine is the sedative agent …”
Section: Discussionmentioning
confidence: 99%
“…Time is of the essence for urgent and emergent procedures-not just to minimize physical harm from the active condition, but to minimize distress for the patient and their family. Delaying procedural sedation for reasons not supported by evidence [23][24][25][26][27][28][29][30][31] may result in extended periods of unremitting pain and anxiety with a negligible decrease in risk and must be avoided.…”
Section: Patient-and Family-centered Carementioning
confidence: 99%